ABOVE AND BELOW GROUND BIOMASS OF ACACIA HYBRID INDIVIDUAL TREE AT LA NGA FORESTRY COMPANY LIMITED, DONG NAI PROVINCE - Thi Ha, Nguyen (Journal of Forestry Science and Technology, 2021)
The study was conducted to determine the above and below ground biomass of Acacia hybrid (Acacia auriculiformis*Acacia mangium) of different diameter classes at La Nga Forestry Company Limited in Dong Nai. A typical standard tree survey method was used to measure fresh biomass, the study cut down 45 trees of different ages and diameters for measuring the fresh biomass with 4 parts including trunk, branches, leaves (above-ground biomass), and roots (below-ground biomass). The analysis of dry biomass was conducted by oven method at 1050C (for stems, roots and branches) and 800C (for leaves). The results showed that the above and below ground biomass of individual trees at different diameter and ages were significantly different. On average, dry biomass above ground of individual plants accounted for 82%, and below ground biomass accounted for 18%. The percentage of biomass of all parts of Acacia hybrid was mainly in the trunk (69%), followed by the roots (18%), branches (10%), and finally the leaves (3%). The total biomass of individual plants fluctuated strongly between diameter classes and increased with diameter, dry biomass was 6.7 - 484 kg corresponding to diameters classes from 4 to 24 cm. The total dry biomass of an individual tree with a diameter of 14 cm and a height of 16.9 m averaged 141.7 kg/plant, of which the above ground part reached 118.0 kg/tree and the below-ground part reached 23.7 kg/tree.